DNA Metabarcoding Reveals Tardigrades' Diversity and Dispersal Patterns in European Freshwater Rock Pools - Matteo Vecchi; Claudio Ferrari; Diego Fontaneto; Jakub Godziek; Ingemar K. Jönsson; Daniel Stec (Journal of Biogeography, 2026)
Aim Freshwater rock pools are ephemeral and fragile habitats that support specialised animal taxa. While distributed worldwide, these habitats are usually neglected and overlooked. We used DNA metabarcoding and metaphylogeographic approaches to study inter and intraspecific tardigrade biodiversity to identify their biogeographic patterns to inform conservation measures. Location Europe. Period Present. Major Taxa Studied Tardigrades. Methods We conducted DNA metabarcoding targeting a fragment of the cytochrome oxidase subunit 1 gene of 163 freshwater rock pools from four sites in Sweden, Poland and Italy to analyse the effect of both short and long distance on their alpha diversity and genetic differentiation. Results A total of 85 tardigrades OTUs (species‐level clusters) were detected, with the most prevalent taxa across all samples being species from the genus Ramazzottius . OTUs richness was mostly driven by a negative relationship with rock pool depth and site‐specific differences. For seven OTUs a phylogeographic analyses revealed a strong founder effect and a variable effect of geographic distance and climate on their population structures. Main Conclusions The high biodiversity and presence of potential specialised taxa highlight the conservation value of freshwater rock pools. While some tardigrade species may be able to easily disperse and have a large geographic range, other species show isolation by distance patterns and their genetic diversity may be negatively affected by habitat loss. Our results call for a bigger effort in identifying, mapping, characterising and protecting freshwater rock pools as underlooked but important habitats.

Phytoremediation by rooted macrophyte Vallisneria spiralis, not biochar amendment, reduces eutrophication from nutrient release in organic-rich sediment of a polluted wetland - Leonardo Morini; Claudio Ferrari; Monia Magri; Sara Benelli; Mindaugas Zilius; Giovanna Visioli; Marco Bartoli (Science of The Total Environment, 2025)

The Adoption of Technological Innovations in the Maritime Industry: A Bibliometric Review - Armand Djoumessi; Alessio Tei; Claudio Ferrari (Journal of Marine Science and Engineering, 2025)
The adoption of technological innovations in the maritime industry is of interest to business, policy, and academic communities. In the last group, this interest has translated into the publication of a large but scattered literature, making it difficult to compare findings and identify the dynamics, structures, and patterns that might inform future research. A comprehensive review of past research on this topic might help achieve this. To date, no such review has been carried out, which is an important gap in the literature that this paper contributes to bridging. Two bibliometric review techniques—co-citation analysis of cited references and bibliographic coupling of documents—are applied to 171 journal articles published between 1999 and February 2025 to answer the following questions: 1. What is the knowledge base of this literature? 2. What are the recent research trends (research fronts) in this literature? The analysis reveals that research on “shore power” dominates both the knowledge base and research fronts. Other key research themes centre on “autonomous shipping”, “blockchain”, and “alternative fuels”. Based on these results, implications for future research are drawn.

Predicting Population Consequences of an Epidemic of High Pathogenicity Avian Influenza on Southern Elephant Seals - Claudio Campagna; Richard Condit; Mariano Ferrari; Julieta Campagna; Elena Eder; Marcela Uhart; Ralph E. T. Vanstreels; Valeria Falabella; Mirtha N. Lewis (Marine Mammal Science, 2025)
The colony of southern elephant seals ( Mirounga leonina ) at Península Valdés (Argentina) grew by 0.9% from 2000 to 2022, reaching a population of 18,000 reproductive females. In 2023, an epidemic of the High Pathogenicity Avian Influenza H5N1 virus led to the death of almost all pups and an unknown number of adults. We tested five scenarios that included complete pup mortality along with varying levels of adult mortality and reduced fertility. Newborn mortality had the smallest impact on the future population due to high natural mortality. Consequences of pup deaths will not appear until 2027, when those lost pups would have first reproduced. Scenarios including mature female mortality had more severe and immediate consequences, with a reduction in the breeding population in 2024 predicted to match the flu death rate. It took about 10 years for the population to readjust to the 2022 age distribution. In scenarios including adult mortality, it will take decades for the population to return to the 2022 level. The 2023 epidemic may thus reverse the conservation status of a population previously having no threats to continued growth.

The Impact of electroanatomical mapping in guiding phased radiofrequency catheter ablation of atrial fibrillation - Giovanni Malanchini; Paola Ferrari; Raul Limonta; Gabriele Ferrari; Cristina Leidi; Claudio Ciampi; Giovanna Donadello; Paolo De Filippo (Next Research, 2025)

Conservation genetics of barbel species (Teleostei, Cyprinidae) facing hybridization and introgression along an elevational gradient in protected areas of northern Italy - Claudio Ferrari; Federica Piccoli; Andrea Voccia; Pietro Maria Rontani; Stefano Leonardi; Alessia Ardenghi; Francesco Nonnis Marzano; Laura Filonzi (Zoologica Scripta, 2025)
The European endemic barbels represent important bioindicators of river quality and are nowadays threatened by changing environmental conditions and hybridization with the invasive alien Barbus barbus . It is therefore fundamental to investigate interactions among species and adaptability to climate changes in protected areas of Northern Apennines. An investigation was carried out considering 248 barbel samples that were analysed for Cytb mitochondrial DNA and 192 at 10 microsatellite loci, to delineate the distribution and population structure of the two native species as well as the impact of invasive B. barbus inside 15 sites of the Natura 2000 network. The complex distribution of the native barbel species was highlighted, together with a significant genetic structure emerging in different populations. Only one site revealed a “pure” population of B. caninus while the other ones showed a high level of hybridization between the different barbel species. For the B. plebejus two “genetically pure” populations were found in the hill‐mountain sector, while the hybridization level resulted in increasing in the lowest altitudinal stretch of watercourses with a consistent contribution driven by B. barbus . We herein present the first evidence of B. barbus introgression along an altitudinal gradient, carried from the lowland water course to mountain stretches driven by B. plebejus migration. B. plebejus is the species that can act as vicariant organism able to transfer the B. barbus genome from the plain habitats into B. caninus genome of the higher altitude waterstreams, as a consequence of habitat shifts due to climate changes and anthropogenic acitivities.

Evapotranspiration of an abandoned grassland in the Italian Alps: Modeling the impact of shrub encroachment - Davide Gisolo; Ivan Bevilacqua; Alessio Gentile; Justus van Ramshorst; Davide L. Patono; Claudio Lovisolo; Maurizio Previati; Davide Canone; Stefano Ferraris (Journal of Hydrology, 2024)

Camera trap surveys of A tlantic F orest mammals: A data set for analyses considering imperfect detection (2004–2020) - Ingridi Camboim Franceschi; Rubem Augusto da Paixão Dornas; Isabel Salgueiro Lermen; Artur Vicente Pfeifer Coelho; Ademir Henrique Vilas Boas; Adriano Garcia Chiarello; Adriano Pereira Paglia; Agnis Cristiane de Souza; Alana Rafaela Borsekowsky; Alessandro Rocha; Alex Bager; Alexander Zaidan de Souza; et al. (Ecology, 2024)
Camera traps became the main observational method of a myriad of species over large areas. Data sets from camera traps can be used to describe the patterns and monitor the occupancy, abundance, and richness of wildlife, essential information for conservation in times of rapid climate and land‐cover changes. Habitat loss and poaching are responsible for historical population losses of mammals in the Atlantic Forest biodiversity hotspot, especially for medium to large‐sized species. Here we present a data set from camera trap surveys of medium to large‐sized native mammals (>1 kg) across the Atlantic Forest. We compiled data from 5380 ground‐level camera trap deployments in 3046 locations, from 2004 to 2020, resulting in 43,068 records of 58 species. These data add to existing data sets of mammals in the Atlantic Forest by including dates of camera operation needed for analyses dealing with imperfect detection. We also included, when available, information on important predictors of detection, namely the camera brand and model, use of bait, and obstruction of camera viewshed that can be measured from example pictures at each camera location. Besides its application in studies on the patterns and mechanisms behind occupancy, relative abundance, richness, and detection, the data set presented here can be used to study species' daily activity patterns, activity levels, and spatiotemporal interactions between species. Moreover, data can be used combined with other data sources in the multiple and expanding uses of integrated population modeling. An R script is available to view summaries of the data set. We expect that this data set will be used to advance the knowledge of mammal assemblages and to inform evidence‐based solutions for the conservation of the Atlantic Forest. The data are not copyright restricted; please cite this paper when using the data.

Metagenomics untangles potential adaptations of Antarctic endolithic bacteria at the fringe of habitability - Claudia Coleine; Davide Albanese; Angelique E. Ray; Manuel Delgado-Baquerizo; Jason E. Stajich; Timothy J. Williams; Stefano Larsen; Susannah Tringe; Christa Pennacchio; Belinda C. Ferrari; Claudio Donati; Laura Selbmann (Science of The Total Environment, 2024)

The trace element distribution in peat soils affected by natural burning events: A proxy of the original composition and metals mobility assessment - Claudio Natali; Mattia Ferrari; Alessandro Bragagni; Gianluca Bianchini; Gian Marco Salani; Riccardo Avanzinelli; Matthias Ghiotto (Science of The Total Environment, 2023)

Role of short germination and milling on physical properties, amino acid and metabolomic profiles of high amylose rice fractions - Maria Eugenia Araujo Silva Oliveira; Luciana Ribeiro da Silva Lima; Millena Cristina Barros Santos; Nathalia Ferrari Fonseca de Sales; Renata Marenda Ferreira; Luiz Claudio Cameron; José Manoel Colombari Filho; Priscila Zaczuk Bassinello; Carlos Wanderlei Piler de Carvalho; Mariana Simões Larraz Ferreira; Cristina Yoshie Takeiti (Food Research International, 2023)

Effect of multifunctional irrigation on grape quality: a case study in Northern Italy - Bianchi Davide; Bolognini Martino; Brancadoro Lucio; Cazzaniga Sara; Ferrari Daniele; Masseroni Daniele; Modina Davide; Ortuani Bianca; Pozzoli Carola; Gandolfi Claudio (Irrigation Science, 2023)
In recent decades, worldwide wine-growing regions have been affected by increasingly more frequent effects of climate change, such as long period of droughts during the growing season, summer heat waves, and late spring frost events, thus causing concern for the grape quality and production. In this context, it is necessary to develop innovative agronomic practices to counter the various negative effects from those extreme weather events, by equipping the vineyards with effective and reliable multifunctional systems, which are also economically sustainable. Particularly, a multifunctional irrigation system can be used to reduce the risk of extreme weather events and, at the same time, to improve quality and quantity of grape production, reducing their inter-annual variability as well, by providing an optimized plant water nutrition. In a vineyard situated south of Lake Garda (Northern Italy), a multifunctional irrigation system equipped with drippers and mini-sprinklers (the latter to protect from both late spring frost and summer high-temperature event) was assessed. The results obtained for the growing season 2020–21 showed that the optimized drip irrigation reduced water consumption without affecting the grape yield, both in quantity and quality. The frost protection operated by mini-sprinklers increased the air temperature at bud’s level of about 1 °C, suggesting a positive effect on plant production. Finally, in 2020, must quality was positively affected by summer sprinkler irrigation, increasing the levels of malic acid and titratable acidity of over 0.7 g L −1 while lowered total soluble solids. Further activities in the 2022 season intend to better assess the water use efficiency of this promising multifunctional system.

Mechanical power normalized to aerated lung predicts noninvasive ventilation failure and death and contributes to the benefits of proning in COVID-19 hypoxemic respiratory failure - Giovanni Musso; Claudio Taliano; Marco De Iuliis; Elena Paschetta; Caterina Fonti; Andrea Ferraris; Marta Druetta; Ines Sarah Vianou; Francesca Ranghino; Federica Riedo; Davide Deangelis; Gloria Tirabassi (EPMA Journal, 2023)

The leaching behaviors of lead, zinc, and sulfate in pyrite ash contaminated soil: mineralogical assessments and environmental implications - Yikai Liu; Simone Molinari; Maria Chiara Dalconi; Luca Valentini; Giulia Ricci; Claudio Carrer; Giorgio Ferrari; Gilberto Artioli (Journal of Environmental Chemical Engineering, 2023)

Carotid artery stenting during endovascular thrombectomy for acute ischemic stroke with tandem occlusion: the Italian Registry of Endovascular Treatment in Acute Stroke - Fabrizio Sallustio; Giovanni Pracucci; Manuel Cappellari; Valentina Saia; Alfredo Paolo Mascolo; Federico Marrama; Roberto Gandini; Giacomo Koch; Marina Diomedi; Federica D’Agostino; Alessandro Rocco; Valerio Da Ros; et al. (Acta Neurologica Belgica, 2023)

Expanding Acutuncus: Phylogenetics and morphological analyses reveal a considerably wider distribution for this tardigrade genus - Matteo Vecchi; Alexandra Tsvetkova; Daniel Stec; Claudio Ferrari; Sara Calhim; Denis Tumanov (Molecular Phylogenetics and Evolution, 2023)

DNA barcoding to assess species identification in museum samples of Amphiliidae and natural samples of Cichlidae from Southern Mozambique - Claudio Ferrari; Erica Tovela; Elisa Taviani; Francesco Nonnis Marzano (Rendiconti Lincei. Scienze Fisiche e Naturali, 2022)
The biodiversity protection and monitorning is one of main goals of natural history musems worldwide. Conservation issues are particularly important for freshwater fish which are one of the most threatened taxa for the consequences of climate change and human activies. In Mozambique freshwater rivers are poorly explored and the impact of aquaculture and human activities on local biodiversity in almost unknown. Here we propose the barcoding analysis of cytochrome c oxidase I (COI) mitochrondrial DNA of 41 frehswater fishes catched in four rivers of southern Mozambique and 53 from a museum collection. As evidence of previous knowledge gaps, barcoding results revealed twenty new haplotypes described for the first time in the taxa Cichlidae and Amphilidae. From a methodological point of view, the barcoding approach demonstrated a critical point connected to the requested 650 bp length of amplified sequences. In fact, high weight genomic DNA is unattainable from museum samples and also in wildlife samples collected in pristine rivers. For this reason we furtherly tested the efficiency of DNA mini-barcoding analysis for 53 fish from a museum collection. The Mini-barcode method retrieved 56.6% of sequences successfully analyzed versus 3% of barcoding. The high performance of this thecniques is discussed in relation to biodiversity monitoring and to fill the taxonomy gaps in museum collections.

First evidence of population genetic structure of the deep-water blackmouth catshark Galeus melastomus Rafinesque, 1810 - Simone Di Crescenzo; Alice Ferrari; Claudio Barría; Rita Cannas; Alessia Cariani; Jim Drewery; Lourdes Fernández-Peralta; Daniela Giordano; Manuel Hidalgo; Vasiliki Kousteni; Ilaria Anna Maria Marino; Daniela Massi; et al. (Frontiers in Marine Science, 2022)
Among the main measures adopted to reduce anthropogenic impacts on elasmobranch communities, understanding the ecology of deep-sea sharks is of paramount importance, especially for potentially vulnerable species highly represented in the bycatch composition of commercial fisheries such as the blackmouth catshark Galeus melastomus . In the present work, we unravelled the first indication of population genetic structure of G. melastomus by using a novel and effective panel of nuclear, and polymorphic DNA markers and compared our results with previous findings supporting high genetic connectivity at large spatial scales. Given the lack of species-specific nuclear markers, a total of 129 microsatellite loci (Simple Sequence Repeats, SSRs) were cross-amplified on blackmouth catshark specimens collected in eight geographically distant areas in the Mediterranean Sea and North-eastern Atlantic Ocean. A total of 13 SSRs were finally selected for genotyping, based on which the species exhibited signs of weak, but tangible genetic structure. The clearcut evidence of genetic differentiation of G. melastomus from Scottish waters from the rest of the population samples was defined, indicating that the species is genetically structured in the Mediterranean Sea and adjacent North-eastern Atlantic. Both individual and frequency-based analyses identified a genetic unit formed by the individuals collected in the Tyrrhenian Sea and the Strait of Sicily, distinguished from the rest of the Mediterranean and Portuguese samples. In addition, Bayesian analyses resolved a certain degree of separation of the easternmost Aegean sample and the admixed nature of the other Mediterranean and the Portuguese samples. Here, our results supported the hypothesis that the interaction between the ecology and biology of the species and abiotic drivers such as water circulations, temperature and bathymetry may affect the dispersion of G. melastomus , adding new information to the current knowledge of the connectivity of this deep-water species and providing powerful tools for estimating its response to anthropogenic impacts.

Desiccation risk favours prevalence and diversity of tardigrade communities and influences their trophic structure in alpine ephemeral rock pools - Matteo Vecchi; Claudio Ferrari; Daniel Stec; Sara Calhim (Hydrobiologia, 2022)
Rock pools are ephemeral freshwater habitats characterized by their small size, well-defined boundaries, and periodic desiccation, making them ideal model systems to answer numerous ecological questions. Although there are numerous studies on rock pool fauna around the world, tardigrades have only rarely been recorded. We conducted the first tardigrade-focused study on rock pools by quantitatively extracting and classifying them from rock pools in the Italian Apennines. Rock pools were divided into three types, based on maximum duration of their inundation period. Following the patterns usually observed with rock pool invertebrates, we tested the hypothesis that desiccation has a negative effect on prevalence, abundance, and diversity of tardigrades, and thus could alter the trophic structure of their communities. In contrast to what is commonly found for other animal groups in the same type of habitat, we found that tardigrades were more diverse and prevalent in shallower, more desiccation prone, rock pools. Moreover, the trophic structure of tardigrade communities was different among the different pool types. Lastly, we also provide DNA barcodes of the most commonly found taxa. Ultimately, our study demonstrates that tardigrade communities in rock pools provide a valuable model system for the study of abiotic factors influencing meiofauna communities.

A study of SARS-CoV-2 epidemiology in Italy: from early days to secondary effects after social distancing - Marco Claudio Traini; Carla Caponi; Riccardo Ferrari; Giuseppe Vittorio De Socio (Infectious Diseases, 2020)

Lime and gypsum combination improves crop and forage yields and estimated meat production and revenue in a variable charge tropical soil - Carlos A. C. Crusciol; Rubia R. Marques; Antonio C. A. Carmeis Filho; Rogério P. Soratto; Claudio H. M. Costa; Jayme Ferrari Neto; Gustavo S. A. Castro; Cristiano M. Pariz; André M. Castilhos; Alan J. Franzluebbers (Nutrient Cycling in Agroecosystems, 2019)

ATLANTIC ‐ PRIMATES : a dataset of communities and occurrences of primates in the Atlantic Forests of South America - Laurence Culot; Lucas Augusto Pereira; Ilaria Agostini; Marco Antônio Barreto de Almeida; Rafael Souza Cruz Alves; Izar Aximoff; Alex Bager; María Celia Baldovino; Thiago Ribas Bella; Júlio César Bicca‐Marques; Caryne Braga; Carlos Rodrigo Brocardo; et al. (Ecology, 2019)
Primates play an important role in ecosystem functioning and offer critical insights into human evolution, biology, behavior, and emerging infectious diseases. There are 26 primate species in the Atlantic Forests of South America, 19 of them endemic. We compiled a dataset of 5,472 georeferenced locations of 26 native and 1 introduced primate species, as hybrids in the genera Callithrix and Alouatta . The dataset includes 700 primate communities, 8,121 single species occurrences and 714 estimates of primate population sizes, covering most natural forest types of the tropical and subtropical Atlantic Forest of Brazil, Paraguay and Argentina and some other biomes. On average, primate communities of the Atlantic Forest harbor 2 ± 1 species (range = 1–6). However, about 40% of primate communities contain only one species. Alouatta guariba (N = 2,188 records) and Sapajus nigritus (N = 1,127) were the species with the most records. Callicebus barbarabrownae (N = 35), Leontopithecus caissara (N = 38), and Sapajus libidinosus (N = 41) were the species with the least records. Recorded primate densities varied from 0.004 individuals/km 2 ( Alouatta guariba at Fragmento do Bugre, Paraná, Brazil) to 400 individuals/km 2 ( Alouatta caraya in Santiago, Rio Grande do Sul, Brazil). Our dataset reflects disparity between the numerous primate census conducted in the Atlantic Forest, in contrast to the scarcity of estimates of population sizes and densities. With these data, researchers can develop different macroecological and regional level studies, focusing on communities, populations, species co‐occurrence and distribution patterns. Moreover, the data can also be used to assess the consequences of fragmentation, defaunation, and disease outbreaks on different ecological processes, such as trophic cascades, species invasion or extinction, and community dynamics. There are no copyright restrictions. Please cite this Data Paper when the data are used in publications. We also request that researchers and teachers inform us of how they are using the data.

Chronic Hippocampal Expression of Notch Intracellular Domain Induces Vascular Thickening, Reduces Glucose Availability, and Exacerbates Spatial Memory Deficits in a Rat Model of Early Alzheimer - Pablo Galeano; María C. Leal; Carina C. Ferrari; María C. Dalmasso; Pamela V. Martino Adami; María I. Farías; Juan C. Casabona; Mariana Puntel; Sonia Do Carmo; Clara Smal; Martín Arán; Eduardo M. Castaño; et al. (Molecular Neurobiology, 2018)

Port Decision Maker Perceptions on the Effectiveness of Climate Adaptation Actions - Adolf K.Y. Ng; Huiying Zhang; Mawuli Afenyo; Austin Becker; Stephen Cahoon; Shu-ling Chen; Miguel Esteban; Claudio Ferrari; Yui-yip Lau; Paul Tae-Woo Lee; Jason Monios; Alessio Tei; et al. (Coastal Management, 2018)

Seroepidemiological survey on Leptospira spp. infection in wild and domestic mammals in two distinct areas of the semi-arid region of northeastern Brazil - Laís Ferrari dos Santos; Maíra Freitas Guimarães; Gisele Oliveira de Souza; Ivo Wesley Gomes da Silva; Josenilton Rodrigues Santos; Sérgio Santos Azevedo; Marcelo Bahia Labruna; Marcos Bryan Heinemann; Mauricio Claudio Horta (Tropical Animal Health and Production, 2017)

Erratum to: Population genetics of pike, genus Esox (Actinopterygii, Esocidae), in Northern Italy: evidence for mosaic distribution of native, exotic and introgressed populations - Andrea Gandolfi; Claudio Ferrari; Barbara Crestanello; Matteo Girardi; Livia Lucentini; Andreas Meraner (Hydrobiologia, 2017)

Population genetics of pike, genus Esox (Actinopterygii, Esocidae), in Northern Italy: evidence for mosaic distribution of native, exotic and introgressed populations - Andrea Gandolfi; Claudio Ferrari; Barbara Crestanello; Matteo Girardi; Livia Lucentini; Andreas Meraner (Hydrobiologia, 2017)

Increased levels of RNA oxidation enhance the reversion frequency in aging pro-apoptotic yeast mutants - Mariarita Stirpe; Vanessa Palermo; Matteo Ferrari; Seweryn Mroczek; Joanna Kufel; Claudio Falcone; Cristina Mazzoni (Apoptosis, 2017)

An integrated, multisensor system for the continuous monitoring of water dynamics in rice fields under different irrigation regimes - Enrico Antonio Chiaradia; Arianna Facchi; Daniele Masseroni; Daniele Ferrari; Gian Battista Bischetti; Olfa Gharsallah; Sandra Cesari de Maria; Michele Rienzner; Ezio Naldi; Marco Romani; Claudio Gandolfi (Environmental Monitoring and Assessment, 2015)

The founding of a southern elephant seal colony - Mariano A. Ferrari; Claudio Campagna; Richard Condit; Mirtha N. Lewis (Marine Mammal Science, 2013)
The only large mainland colony of southern elephant seals ( Mirounga leonina ) is on Península Valdés, at 42°S, in Argentine Patagonia. Censuses of pups have been carried out regularly there since 1970, and the population grew five‐fold by 2010. Here we use Bayesian modeling tools to make rigorous estimates of the rate of population growth, r , and to estimate survival and recruitment parameters that could account for the growth, incorporating observation error across different census methods. In the 1970s, r = 8%/yr, but has slowed to

Exploring the effects of seasonality and chemical pollution on the hepatopancreas transcriptome of the M anila clam - Massimo Milan; Serena Ferraresso; Claudio Ciofi; Guido Chelazzi; Claudio Carrer; Giorgio Ferrari; Lino Pavan; Tomaso Patarnello; Luca Bargelloni (Molecular Ecology, 2013)
The assessment of marine environmental health is a complex but fundamental task both for ecosystem conservation and food safety related to the human consumption of marine products. Manila clams inhabiting the V enice L agoon constitute an excellent case study for evaluating the effects of complex mixtures of industrial and urban effluents on aquatic organisms. Clams were collected in different seasons at four locations within the V enice L agoon. The sampling sites were characterized by a range of pollutant concentrations and included P orto M arghera, a highly polluted industrial area where clam harvesting for human consumption is strictly forbidden. Pooled soft tissues were subjected to mass spectroscopy analysis to measure the concentrations of PCDD s/ PCDF s/ PCB s‐ DL , PCB s, PBDE s, HCB and PAH s, and pooled digestive gland samples were used for gene expression profiling. While seasonal variation was found to be responsible for the largest proportion of transcriptional changes, significance analysis of microarrays quantitative correlation analysis identified 162 transcripts that were correlated with at least one class of chemicals measured in the samples from the four different sampling sites. Prediction Analysis of Microarrays ( PAM ) identified a minimal set of seven genes that correctly assigned samples collected in the restricted polluted area ( P orto M arghera), independent of the season in which they were collected. An integrated approach combining transcriptomics and chemical analyses of the M anila clam provided a global picture of how M anila clams respond to complex mixtures of xenobiotics and their interplay with other biotic and abiotic factors. We were also able to identify gene expression signatures for different classes of chemicals and a set of robust biomarkers of exposure to these chemicals.

Eye movements and bisection behavior in spatial neglect syndrome: representational biases induced by the segment length and spatial dislocation of the stimulus - Michela Balconi; Matteo Sozzi; Chiara Ferrari; Luigi Pisani; Claudio Mariani (Cognitive Processing, 2012)

α- and β-Adducin polymorphisms affect podocyte proteins and proteinuria in rodents and decline of renal function in human IgA nephropathy - Mara Ferrandi; Daniele Cusi; Isabella Molinari; Lucia Del Vecchio; Cristina Barlassina; Maria Pia Rastaldi; Francesco Paolo Schena; Fabio Macciardi; Carmelita Marcantoni; Dario Roccatello; Luanne L. Peters; Silvia Armelloni; et al. (Journal of Molecular Medicine, 2010)

Effects of calcium in the nitrogen-fixing symbiosis between actinorhizal Discaria trinervis (Rhamnaceae) and Frankia - Claudio Valverde; Alejandro Ferrari; Luis Gabriel Wall (Symbiosis, 2009)

Interdependence of social structure and demography in the southern elephant seal colony of Península Valdés, Argentina - Mariano A. Ferrari; Mirtha N. Lewis; Miguel A. Pascual; Claudio Campagna (Marine Mammal Science, 2009)
Southern elephant seals breed at Península Valdés (PV, Argentina) along 200 km of coastline. Annual pup counts at peak breeding season for the entire colony increased from 12,113 in 1995 to 14,350 in 2006. Two demographic subunits were identified in the North and South of PV with different trends in births numbers, sex ratios and harem sizes. Birth numbers increased in the South, but decreased sharply in the North. To explain the trends in the colony and subunits, a population model was proposed that integrates social structure (harem size and sex ratio) in a fertility function that quantifies the effects of the social structure on the number of births. We found that a better fit to census data results from our model compared to a linear one (χ 1 2 = 4.027, P = 0.045) . The model was then used to test alternative hypotheses about the role of recruitment and migration on the dynamic of the two subunits. Results indicated the relevance of considering social structure in population models of gregarious and polygynous species, and is an additional tool for comparative studies between populations of elephant seals where long term census are available.

Der Einfluß des Wirtschaftswachstums im Mittelmeerraum auf das europäische Hafen- und Verkehrssystem - Enrico Musso; Claudio Ferrari (Standort, 2001)

Tissue inhibitors of metalloproteases: Regulation and biological activities - Gianfranco Fassina; Nicoletta Ferrari; Claudio Brigati; Roberto Benelli; Leonardo Santi; Douglas M. Noonan; Adriana Albini (Clinical & Experimental Metastasis, 2000)